2006
DOI: 10.1111/j.1365-2621.2006.tb12406.x
|View full text |Cite
|
Sign up to set email alerts
|

Aroma Impact Compounds in Three Citrus Oils: Cross‐matching Test and Correspondence Analysis Approach

Abstract: Twenty‐three odor chemicals from 3 Citrus essential oils (lemon, Valencia orange, and Citrus sudachi) were selected as the potent character‐impact compounds on the basis of their limited odor unit values, and then every chemical was cross‐matched by sensory test to the 3 oils to attribute each aroma character to 1 of the 3 Citrus oils. The matching‐frequency data (ratio data) obtained was subjected to correspondence analysis and graphed on a diagram. Consequently, it was found that the aroma character of lemon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 23 publications
0
13
0
Order By: Relevance
“…With demands from consumers to find alternatives to chemical‐based washing detergents for food application, limonene is potentially an ideal alternative. More studies on primary food are required to assess the changes in organoleptic properties after the application of limonene, although it has been reported that some components including limonene were found to be neutral and have no effect on aroma quality . The other factor that must be considered with the use of limonene on food is that it can play a role in the formation of secondary aerosols and form pollutants .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With demands from consumers to find alternatives to chemical‐based washing detergents for food application, limonene is potentially an ideal alternative. More studies on primary food are required to assess the changes in organoleptic properties after the application of limonene, although it has been reported that some components including limonene were found to be neutral and have no effect on aroma quality . The other factor that must be considered with the use of limonene on food is that it can play a role in the formation of secondary aerosols and form pollutants .…”
Section: Resultsmentioning
confidence: 99%
“…More studies on primary food are required to assess the changes in organoleptic properties after the application of limonene, although it has been reported that some components including limonene were found to be neutral and have no effect on aroma quality. 24 The other factor that must be considered with the use of limonene on food is that it can play a role in the formation of secondary aerosols and form pollutants. 25 In order to ensure food safety and reduce the negative impact to a minimum, accurate concentration tests need to be carried out to find the lowest concentration of limonene that has the greatest effect.…”
Section: Effects Of Washing On the Removal Of Pesticide Residue In Grmentioning
confidence: 99%
“…Several publications have addressed this concern (Kim and others 1995; Burt 2004; Fernandez‐Lopez and others 2005; Holley and Patel 2005; Fisher and Phillips 2006; Fisher and others 2007; Kotzekidou and others 2007; Mandalari and others 2007; O'Bryan and others 2008). Researchers are also doing odor cross‐matching tests to determine compounds responsible for flavor and they have found that some components are neutral, including limonene, l‐octanol, and dodecanal (Chida and others 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Citral is thought to be a potent characterimpact compound and a key component in lemon oil, although linalool is the overall aroma compound in orange [46].…”
Section: Foodmentioning
confidence: 99%